Design and construction of foundations on wetlands - V. Kulikov, Aleksandr (International Journal of Engineering and Technology, 2018)
The paper reports the excess pore pressures effect (that arises in shrinkable peat foundation) on its own physical mechanical characteristics. The authors suggested the upgraded assembly scheme of the soil pressure sensors (load cells). The laboratory research of the water-saturated macro peat sample was made in compression conditions with â€œground lockâ€ and modeling of the experiment with Plaxis 2D software system. The unit deformation-pressure graph and excessive pore pressure against time in different steps of load graph were built and based on this findings.Â